Voltamogram Stainless Steel/Fe-Co-Ni dalam Media Tepung Ubi Jalar (Ipomoea batatas L.) - Isana Supiah Yosephine Louise; Heru Pratomo Aloysius; Sulistyani Sulistyani (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2018)
Cyclic voltammogram of stainless steel/Fe-Co-Ni on base condition and on various sweet potato starch concentration could be used to study the electrocatalyst activity of stainless steel/Fe-Co-Ni. The efficiency is derived from the point of view of product and energy required, for instance comparing between stainless steel/Fe-Co-Ni and stainless steel.The research had conducted water electrolysis on base condition with several conditions, such as addition of 5 grams NaHCO3 per liter of water, sweet potato starch as medium on various concentration (0 - 10 grams per liter of water), and stainless steel/Fe-Co-Ni as a working electrode. The research methodology which is used is cyclic voltammogram using eDAQ EChem as the voltameter instrument.Based on the cyclic voltammograms, it could be concluded that sweet potato starch causes covering around the electrode surfaces so water molecule splitting process would be obstructed. The optimum covering point is occurred on the addition of 9 grams sweet potato starch per liter of water. The optimum condition is occurred on the addition of 4 grams sweet potato of starch per liter of water; with product efficiency is 1.62 times and energy saving as much as 6.90% compared with the utilization of stainless steel as electrode. Keywords: voltammogram, sweet potato, stainless steel/Fe-Co-Ni, covering, efficiency.